Foucault Dan Diskursus Media Siber - Poppy Febriana; Ratih Puspa (MediaTor (Jurnal Komunikasi), 2021)
The availability of cybermedia offers many options that vary for discovering and consuming information similar to the ability to generate it. Cybermedia has also given rise to new methods for people to interact and build relationships in society, posing problems for researchers in the communication study field, particularly in dissecting new kinds of multi-modal communication. The research objective is to learn more about how Michel Foucault's discourse analysis applies to the cybermedia discourse. The findings of this study show that Foucault's notions, as found in The Birth of the Clinic, The Archeology of Knowledge, and Technology of the Self, are still relevant in addressing the difficulties of cybermedia research. The Foucaultian approach to social media focuses on sharing processes, which are the foundation of social media. Another aspect of Foucault's media philosophy is "constant awareness and visibility."